การสำรวจผลกระทบของไฟกระพริบเตือนที่มีต่อพฤติกรรมการขับขี่ ที่ทางแยกในเขตเทศบาลเมืองเชียงใหม่ - เกิดศิริ, ศิขรินทร์; กรประเสริฐ, นพดล (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Road traffic deaths in Thailand are mostly occurred in urban areas with a large number of motorcyclists. One of the hazardous locations is the intersections with no traffic control in urban areas, or known as Wat Jai intersection, where motorcycle accidents are frequent and severe. The major causes of accidents are the insufficient visibility of intersections and sometimes no traffic lights at night leading to indecisive driving while traveling through an intersection. Flashing warning lights are among safety countermeasures widely used to warn road users to be aware of an intersection and reduce the speed while approaching at an intersection. Flashing warning lights are currently implemented in 19 locations in Chiang Mai municipality area. This study aims to examine the effectiveness of flashing warning lights at intersections by performing the before-and-after observation study. The indicators used in this study are the speed profile of vehicles passing intersections, the time to collision, and the risk of collision.